Assessing the impact of greenhouse gas emissions on economic profitability of arable, forestry, and silvoarable systems - Kaske, Kristina J.; García de Jalón, Silvestre; Williams, Adrian G.; Graves, Anil (MDPI, 2021)
This study assesses the greenhouse gas (GHG) emissions and sequestration of a silvoarable system with poplar trees and a crop rotation of wheat, barley, and oilseed rape and compares this with a rotation of the same arable crops and a poplar plantation. The Farm-SAFE model, a financial model of arable, forestry, and silvoarable systems, was modified to account for life-cycle greenhouse gas emissions. Greenhouse gas emissions from tree and crop management were determined from life-cycle inventories and carbon storage benefits from the Yield-SAFE model, which predicts crop and tree yields in arable, forestry, and silvoarable systems. An experimental site in Silsoe in southern England served as a case study. The results showed that the arable system was the most financially profitable system, followed by the silvoarable and then the forestry systems, with equivalent annual values of EUR 560, 450 and 140 ha−1, respectively. When the positive and negative externalities of GHG sequestration and emissions were converted into carbon equivalents and given an economic value, the profitability of the arable systems was altered relative to the forestry and silvoarable systems, although in the analysis, the exact impact depended on the value given to GHG emissions. Market values for carbon resulted in the arable system remaining the most profitable system, albeit at a reduced level. Time series values for carbon proposed by the UK government resulted in forestry being the most profitable system. Hence, the relative benefit of the three systems was highly sensitive to the value that carbon was given in the analysis. This in turn is dependent on the perspective that is given to the analysis.
Keywords: regulatory ecosystem services; carbon sequestration; GHG emissions; life-cycle inventory; cost-benefit analysis